2014
DOI: 10.1002/oti.1371
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Activity Participation as Predictor of Quality of Life in Korean Urban-dwelling Elderly

Abstract: This study investigated participation in leisure activities in urban-dwelling elderly persons in Korea and its role in predicting quality of life. The participated activities over a 48-hour period were recorded by each participant, and amount of participated time for each activity was calculated. Correlational analysis examined the relationship between the degree of participation in domains of leisure activity and quality of life. Multiple regression analysis was conducted to determine which leisure activity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 9 publications
6
35
1
5
Order By: Relevance
“…15 A study of urban-dwelling Korean older adults found that leisure activity was the strongest predictor of quality of life. 32 These studies are consistent with our findings, which showed that continuous participation in leisure/sports clubs had positive effects on quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…15 A study of urban-dwelling Korean older adults found that leisure activity was the strongest predictor of quality of life. 32 These studies are consistent with our findings, which showed that continuous participation in leisure/sports clubs had positive effects on quality of life.…”
Section: Discussionsupporting
confidence: 93%
“…This supports previous findings, which suggested that community-based groups that are interest-focused encouraged older adults' participation (Andonian & MacRae, 2011;Berger, McAteer, Schreier, & Kaldenberg, 2013;Lee, Lee, & Park, 2014;Ormsby, Stanley, & Jaworski, 2010;Richeson, Buettner, McKenzie, Fitzsimmons, & Keller, 2006). Previous research also suggested that designing groups to promote the development or maintenance of friendships, health and interests encourages community participation by older adults (Andonian & MacRae, 2011;Dickens, Richards, Greaves, & Campbell, 2011;Nicholson, 2012).…”
Section: Discussionsupporting
confidence: 89%
“…A relação entre a prática de exercício físico, a qualidade de vida e o envelhecimento bem-sucedido também tem sido amplamente estudada (Cavalcanti, et al, 2016;Choi, Lee, Lee, & Jung, 2017;Gutiérrez, et al, 2018;Kahana, et al, 2005;Kolt, Driver, & Giles, 2004;Lee, Lee, & Park, 2014). São consideráveis as evidências de que a prática de exercício físico é um forte preditor de envelhecimento bem-sucedido (Kolt, et al, 2004), ao atuar como um fator preventivo/moderador de doença e de incapacidade nos indivíduos mais velhos (Kahana, et al, 2005;Lee, et al, 2014) pelo fortalecimento da sua condição física e dos laços sociais, em particular se a atividade for praticada por lazer (Gutiérrez, et al, 2018). A prática de exercício físico também parece contribuir de forma positiva para o bem-estar psicológico (Chung, Zhao, Liu, & Quach, 2017;Gutiérrez, et al, 2018) e percepção de qualidade de vida (Choi, et al, 2013;Horder, Skoog, & Frändin, 2013).…”
Section: Envelhecimento Bem-sucedido Como Processo Interativo E Multiunclassified